CURRENT SITUATION AND TRENDS IN HERBAL MEDICINE DISPENSING IN SONGKHLA PROVINCE (2020-2024) - Chantarapon, Patama; Bunpean, Aumpol (Journal of Faculty of Physical Education, 2025)
This research aims to: 1) investigate the top 10 most commonly dispensed herbal medicines in Songkhla Province during the fiscal year 2024, and 2) analyze trends in herbal medicine dispensing over the past five years. Secondary data were collected from Thailand's Health Data Center (HDC) program. The findings revealed that: 1. The top 10 most frequently dispensed herbal medicines in 2024 were Makham Pom (Phyllanthus emblica) cough syrup, Prasa Ma Waeng tablets, Makham Pom compound cough syrup (Formula 1), Senna herbal tea, Andrographis paniculata capsules, turmeric capsules, Ma Waeng lozenges, Phlai cream, herbal compress, and Thao Wan Priang capsules. The dispensing trends from 2020 to 2024 showed an increasing trend in the use of certain herbal medicines, particularly Makham Pom cough syrup, Andrographis paniculata, Phlai, and herbal compresses. Notably, in 2024, there was a significant increase in the dispensing of herbal compresses and Ma Waeng lozenges. The growing trend of herbal medicine dispensing in Songkhla Province reflects increased public interest and improved accessibility to herbal treatments. Relevant authorities should develop policies that address public demand, promote safe and effective use of herbal medicines, and further study their safety and potential side effects to ensure sustainable and responsible use.